PENINGKATAN KEPERCAYAAN DIRI ANAK MELALUI PERMAINAN KUCING DAN TIKUS DI TK SAYANG IBU TAHUN 2019 - Hinggil Permana; Rina Syafrida (Journal of Early Childhood Education (JECE), 2019)
This research is conducted to improve children's confidence in TK Sayang Ibu, Bekasi. This research uses action research method. The research subjects consisted of 8 boys and 12 girls, the research procedure is carried out in 2 cycles with 3 meetings in each cycle. The result shows that the kucing dan tikus game can increase the confidence of children of group A in TK Sayang Ibu. The increment happens from first cycle  53,43% to second cycle  77,5%